How has COVID-19 affected the intention to migrate via the backway to Europe and to a neighboring African country? Survey evidence and a salience experiment in The Gambia - Tijan L. Bah; Catia Batista; Flore Gubert; David McKenzie (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
The COVID-19 pandemic has resulted in border closures in many countries and a sharp reduction in overall international mobility. However, this disruption of legal pathways to migration has raised concerns that potential migrants may turn to irregular migration routes as a substitute. We examine how the pandemic has changed intentions to migrate from The Gambia, the country with the highest pre-pandemic per-capita irregular migration rates in Africa. We use a large-scale panel survey conducted in 2019 and 2020 to compare changes in intentions to migrate to Europe and to neighboring Senegal. We find the pandemic has reduced the intention to migrate to both destinations, with approximately one-third of young males expressing less intention to migrate. The largest reductions in migration intentions are for individuals who were unsure of their intent pre-pandemic, and for poorer individuals who are no longer able to afford the costs of migrating at a time when these costs have increased and their remittance income has fallen. We also introduce the methodology of priming experiments to the study of migration intentions, by randomly varying the salience of the COVID-19 pandemic before eliciting intentions to migrate. We find no impact of this added salience, which appears to be because knowledge of the virus, while imperfect, was already enough to inform migration decisions. Nevertheless, despite these decreases in intentions, the overall desire to migrate the backway to Europe remains high, highlighting the need for legal migration pathways to support migrants and divert them from the risks of backway migration.
Keywords: F22; O15; J61; C93; 330; Migration intentions; COVID-19 Pandemic; Priming and Salience Experiments; Backway migration; The Gambia